precal

posted by .

cotxsinx=cosx

• precal -

cotx=cosx/sinx
Therefore, (cosx/sinx)sinx=cosx
cosx=cosx

Similar Questions

1. Math

Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 - …
2. Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
3. precal

4(sinx)(cosx)+2(sinx)-2(cosx)-1=0 Find x in radians I can't figure this out?
4. Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] = [cosx(1-sinx]/[cosx(1+tanx] …
5. precal

1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a negatvie:( …
6. precal

1-cosx/1+cosx=(cotx-cscx)^2
7. precal

please help i can't find the answer for this question. i can only manipulate one side of the equation and the end result has to equal the other side. Problem 1. ((1 + sinx)/cosx) + (cosx/(1 + sinx)) = 2secx
8. precal

fixed typo ((sinx + cosx)/(1 + tanx))^2 + ((sinx - cosx)/(1 - cotx))^2 = 1
9. Precal

Verify the identity: sin^(1/2)x*cosx - sin^(5/2)*cosx = cos^3x sq root sin x I honestly have no clue how to approach the sin^(5/2)*cosx part of the equation
10. Precal/Math

How do i get the left side to equal the right hand side?

More Similar Questions